Modified prone ventilation treatment and nursing for a elderly patient with pulmonary injury after surgery for suppurative cholecystitis (1例老年化脓性胆囊炎术后合并肺损伤患者实施改良俯卧位通气的护理体会) - LI Xueyan (李学艳); LIU Shuhua (刘书华); YANG Siwen (杨思雯); LIU Hongjin (刘宏锦) (中西医结合护理)
This paper summarized the modified prone ventilation treatment and nursing for a elderly patients with pulmonary injury after surgery for suppurative cholecystitis. Comprehensive nursing interventions were carried out including vital signs observation, sedation and analgesia management, management of modified prone position, nursing cooperation of superficial sputum aspiration, nursing of pressure injuries, nursing of catheter blockage and dislocation, and psychological care. The comprehensive nursing is potentially effective to relieve the symptoms of pulmonary injury and ensure the successful withdraw of ventilation. (本文总结1例老年化脓性胆囊炎术后合并肺损伤患者实施改良俯卧位通气的护理经验。通过的严密观察生命体征、镇静镇痛的管理、改良俯卧位细节管控、俯卧位吸痰时浅吸痰的护理、预防压力性损伤的护理、导管堵塞及管路滑脱的护理以及心理护理等, 有效改善老年化脓性胆囊炎术后合并肺损伤患者症状, 有助于患者顺利脱离有创呼吸机治疗。)